Metode Al-Qur’an Membaca Realitas: Analisis Tafsir Sosial - Nashuddin Nashuddin (Ulumuna, 2011)
Al-Qur’an texts never change. however, the way people interpret them can vary in line with space and time changes. Therefore, al-Qur’an is always open to be analysed, percepted, and intepreted in a range of tools, methods, and approaches to reveal its content truth. Hence, a range of interpretative methods can be employed to bring forward the deep meaning of al-Qur’an. The substance of al Qur’an themselves indicate the logic closeness of normative authority with objective social realities. Finding out the similarities and relevances among texts and contexts is, then, a challenge faced by al-Qur’an analysts. Such challenge has led to various methods and interpretation in line with the raising dynamics and debates. This all happen to give responses and solutions to the raising social problems.